Textual Analysis of the Chronicle of King BÃ¤kaffa (1721 â1730) - Nekatibeb, Abeselom (International Research Journal of Management, IT & Social Sciences, 2015)
Many and different manuscript were produced for centuries using GÉÊ¼Éz the classical language of Ethiopia, including the royal chronicles. The chronicle of king BÃ¤kaffa (1721 -1730) was composed in GÉÊ¼Éz which was published under the title of Annals Rine BÃ¤kaffa.by Ignazio Guidi in 1903. It is originally written by AzaÅ¾i Sinoda and his son KÇnfÃ¤ Mikael. The chronicle was not analyzed philologically. The main objective of this study is to show the content of the chronicle and to give brief textual analysis. By doing this I have tried to analyzed the influence of Amharic words, linguistics differences, and biblical allusions